2018
DOI: 10.1016/j.memsci.2018.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of support-layer deformation on the intrinsic resistance of thin film composite membranes

Abstract: It is commonly believed that the overall permeation resistance of thin film composite (TFC) membranes is dictated by the crosslinked, ultrathin polyamide barrier layer, while the porous support merely serves as the mechanical support. Although this assumption might be the case under low transmembrane pressure, it becomes questionable under high transmembrane pressure. A highly porous support normally yields under a pressure of a few MPa, which can result in a significant level of compressive strain that may si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…4B to be independent of P h , signifying intrinsic structure of the polyamide is fundamentally unaltered. Preservation of the polyamide structure is further supported by a previous study which reported only marginal morphological change of the active layer under mechanical compression of 40 bar [42].…”
Section: Active-support Interface Of Osmotic Membranes Under Hydraulisupporting
confidence: 75%
“…4B to be independent of P h , signifying intrinsic structure of the polyamide is fundamentally unaltered. Preservation of the polyamide structure is further supported by a previous study which reported only marginal morphological change of the active layer under mechanical compression of 40 bar [42].…”
Section: Active-support Interface Of Osmotic Membranes Under Hydraulisupporting
confidence: 75%
“…For thin-film composite membrane the flux drop due to compaction of membrane structure according to [29] is observed under applied pressures of 0.5-1.45 MPa. Although in current study in particular cases the applied pressure was in mentioned above range, the duration of continuous operation was no longer than 180-300 s, therefore it may assume that impact of compaction to membrane resistance was negligible.…”
Section: Determination Of Concentration Polarization Layer Resistancementioning
confidence: 98%
“…High trans-membrane pressure condition 3,45 Resistance from porous support layer Porous layer with small pores and porosity, whereby resistance in porous layer as compared to the selective membrane barrier exceeds 10% 46,47 Composite membrane that has different intrinsic material property towards gas transport 7,48 Physical aging All glassy amorphous polymeric membranes 49 temperatures using gas transport behavior during initial aging time 58 or variable membrane permeance attributed to physical aging at constant operating temperature (308.15 K), 34 which highlights the research gap that limited work has been available that addresses the effect of operating temperature towards physical aging. In actual industrial application, feed gas can be operated within the range 35-55 ∘ C, which are typical operating temperatures encountered in membrane separation 34,59,60 since it is much lower than the glass transition temperature of polymeric membrane, which remains it at glassy-like condition 61 to perform separation based on sorption and diffusion of gas penetrants.…”
Section: Deformation Of Hollow Fibersmentioning
confidence: 99%
“…In order to focus on merely quantifying the importance of implementing physical aging to the separation performance of polymeric membranes, the membrane system under study has to be operated under condition whereby the other non‐ideal effects as highlighted in Table can be isolated. The operating condition in which each of the non‐ideal effect is significant has been summarized in Table . To minimize the accumulated impact from other non‐ideal effects that have arisen in majority from high trans‐membrane pressure, a pressure slightly higher than atmospheric condition (0.30 bar‐g) has been adopted for the feed stream in our membrane system under study, while the permeate side has been maintained at vacuum condition to create a pressure driving force for separation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation